Impact of Health Education on Breadfruit Flour as a Carbohydrate Alternative for Diabetes - Nida, Khairun; Junaedi, Junaedi; Fajri, Purnama; Darmawan, Syarif; Isria, Tazkiyatan (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
Diabetes mellitus (DM) is a global health problem that is also a public health challenge in Indonesia, and the prevalence of DM has increased significantly. A healthy lifestyle is currently being promoted to prevent diabetes and control the disease, both through food and exercise. One alternative food ingredient to replace rice and wheat flour with a low glycemic index is breadfruit. Breadfruit has a glycemic index of 23-60 compared with wheat, so it can control blood sugar levels. The purpose of this activity is to provide knowledge about diabetes mellitus and healthy eating patterns or diets and to be able to make food for DM sufferers. The target of this activity is the mothers of cadres from all sub-districts in Utan Kayu Utara Village. The method of implementing the activity is through direct education and showing several videos on how to process breadfruit flour. Participants consisted of 30 cadres. They asked a lot of questions and discussed the material given enthusiastically. There was an increase in cadre knowledge about DM from 51 to 76 points. They were able to utilize breadfruit flour as an alternative source of carbohydrate nutrition for DM patients because they can make various cakes and snacks with a low glycemic index.